Development of Glutathione Production Technology Based on Designed Active Yeast Overproducers - Yurkiv, M.T.; Kurylenko, O.O.; Vasylyshyn, R.V.; Dmytruk, K.V.; Martynyuk, N.B.; Skorohod, V.V.; Sybirny, A.A. (Science and Innovation, 2024)
The Hansenula polymorpha recombinant strain overexpressing both GSH2 gene encoding γ-glutamyl-cysteine-synthetase and MET4 gene encoding the transcription activator of genes involved in cysteine (precursor of glutathione) biosynthesis has been obtained using metabolic engineering approaches. The recombinant strain is characterized by significantly increased glutathione output as compared with in vitro wild-type strain. Conditions for efficient glutathione production by recombinant H. polymorpha strain have been optimized. A semi-industrial model for glutathione production using the designed H. polymorpha overproducer has been developed.